Plyometric exercises: optimizing the transfer of training gains to sport performance - Duchateau, J.; Amiridis, I. G. (Exercise and Sport Sciences Reviews, 2023)
Rapid force production and its transmission to the skeleton are important factors in movements that involve the stretch-shortening cycle. Plyometric exercises are known to augment this cycle and thereby improve the neuromechanical function of the muscle. However, the training exercises that maximize translation of these gains to sports performance are not well defined. We discuss ways to improve this transfer.